Fitoquímica e avaliação das atividades anti-inflamatória e antinociceptiva de Lippia lacunosa Mart. & Schauer. - Gizzelle Delfino Araújo Ladeira (2019)
Lippia lacunosa is an endemic plant in the Serra do Espinhaço/MG region, popularly known as “chá de pedereste” and rosmaninho. This species has a characteristic mango aroma and has wide traditional use, but it is little studied. Biomonitoring studies have already demonstrated the anti-inflammatory and antinociceptive activities of Lippia species. Thus, the objective of the present work was to evaluate the micromolecular composition and the antiinflammatory and antinociceptive activities of the extracts hexane and ethanolic, essential oil and fraction containing major substance (s) obtained from the leaves of L. lacunosa. The chemical composition of the essential oil was investigated by gas chromatography coupled to mass spectrometry (CG-MS) and the main constituents found were the monoterpenes myceno (13.81%), linalol (6.84%) and myrcenone (25.44%) and sesquiterpenes elemol (7.30%), espatulenol (3.15%), among others. The essential oil was fractionated by chromatographic method and the OEF33 fraction was selected for evaluation of the biological activity. In the models of paw edema and mechanical allodynia induced by carrageenan (600 μg, 30 μL, i.pl.), the administration of the ethanolic extract at the doses of 25, 50 and 100 mg / kg, po) did not significantly altered the paw edema of the Swiss mice. In contrast, administration of the hexane extract, essential oil (50 or 100 mg / kg, p.o.) or OEF33 fraction (10 mg / kg, p.o.) reduced paw edema. Ethanolic extract (100 mg / kg) reduced mechanical allodynia only at the second hour of evaluation. On the other hand, the hexane extract (50 or 100 mg / kg), essential oil (100 mg / kg), as well as the OEF33 fraction (10 mg / kg) reduced mechanical allodynia throughout the evaluation period. The hexane extract, essential oil and OEF33 fraction also reduced the heat induced nociceptive response. The motor activity of the animals, evaluated by the residence time in the rotating rod, was not affected by the administration of the vegetal derivatives and OEF33. The results demonstrate the remarkable activity of the hexane extract, essential oil and OEF33 fraction in models of inflammation and nociceptive and inflammatory pain. The elucidation of the composition of the essential oil and the demonstration of the activity of L. lacunosa in experimental models of inflammation and pain can help in the validation of the ethnopharmacological use, aiming the evaluation of the species as a candidate for the phytotherapeutic drug or phytopharmaceutical in the treatment of patients with inflammatory and painful conditions.